Effects of context on the entrepreneurial intent of female students from the United Arab Emirates. Issue 6 (8th July 2019) - Vracheva, Veselina P.; Abu-Rahma, Ali; Jacques, Paul
Abstract : Purpose: The purpose of this paper is to explore the extent to which contextual factors outlined in the theory of planned behavior (TPB) affect entrepreneurial intent (EI) of female students in the United Arab Emirates. Design/methodology/approach: This paper presents a hierarchical regression analysis utilizing data from a university in the UAE. Findings: The study indicates that prior and current family business exposure to entrepreneurship does not affect the EI of female students from the UAE. However, the family affects EI via the family norms. More exposure to business classes and the subjective norms from the university are not significant predictors of EI, and perceived behavioral control is the strongest contextual predictor of EI. Research limitations/implications: The study was limited to the UAE and to a small sample of female students from a single university; therefore, the findings should be interpreted with caution. Practical implications: The study points to opportunities within the university environment to design more robust curricula that offer female students opportunities to boost their confidence in the ability to start up and manage a business. Originality/value: The paper is the first of its kind to apply the TPB to the context of female students from the UAE.